Elective delivery of women with a previous unexplained intra-uterine fetal death at term (≥ 39 weeks) : a prospective cohort study at Tygerberg Hospital, South Africa - Oberholzer, Leana (Stellenbosch : Stellenbosch University, 2015)
Thesis (MMed)--Stellenbosch University, 2014.